Growth and Analysis of Nanostructured CuInSe2-ZnIn2Se4 Solid Solutions: Their Electrical and Photoelectrical Properties. (2015) - Bozhko, V.V.; Novosad, O.V.; Parasyuk, O.V.; Kozer, V.R.; Vertelis, V.; Kažukauskas, V.
Abstract: We report growth and investigation of structural and (photo−)electrical properties of CuInSe2 – ZnIn2 Se4 semiconductor crystals, grown by the horizontal Bridgman method. Their optical bandgap was evaluated from the absorption spectra. It increased monotonously from 1 eV up to 1.08 eV at 300 K with increasing amount of ZnIn2 Se4 in the range of 5–20 mol%. All crystals had n -type electrical conductivity. The solid solutions containing 5–10 mol% ZnIn2 Se4 had demonstrated weak temperature dependence of the electrical conductivity, high electron density and low photoconductivity. This evidences their nearly degenerate state. In the crystals with 15 and 20 mol% ZnIn2 Se4 a variable range hopping conduction mechanism was found to dominate between ∼30 K and 110 K. Above 130 K it was changed by a thermally activated conductivity. The donor activation energy for the samples with 15 and 20 mol% ZnIn2 Se4 were 0.018 eV and 0.04 eV, respectively. The characteristic feature of the spectral distribution of their photoconductivity at 30-70 K is presence of a narrow peak at 1160 – 1190 nm.